Harmonisasi Regulasi Nasional Dengan Standar Internasional Dalam Proyek Multinasional - Anggoro, Prastiwo (Syntax Corporation, 2026)
The global economy is interdependent, as reflected in the US-China trade war in 2025, which increased the value of Foreign Direct Investment in the first quarter of 2025 by 15.9% compared to the previous year. However, based on the Ease of Doing Business (EoDB) Index, Indonesia is still below Vietnam and Thailand, especially in the legal certainty sector. Therefore, harmonization is needed on the legal side, especially construction laws and standards related to multinational and multi-international projects for construction service actors (service owners and service providers, both contractors and consultants) so that Indonesia can ensure ease of investment from a legal perspective amidst global uncertainty due to the trade war.